'Fake News' in Seventeenth-Century France: The Case of Le Mercure galant. Issue Volume 257(2022)Issue Supplement 16 (31st October 2022) - Steinberger, Deborah
Abstract: Le Mercure galant, one of France's first newspapers, is notable for its diverse content: politics and foreign affairs, court news, science and medicine, the arts and literature. Directed by Jean Donneau de Visé from its inception in 1672 until his death in 1710, this influential and innovative monthly publication circulated throughout France and beyond its borders. The Mercure 's tendency to blur the lines between truth and fiction, between history and propaganda, and between information and entertainment, makes it an instructive case study in early modern 'fake news'. Donneau de Visé, a self-styled royal historiographer and the beneficiary of a generous royal pension, dedicated his periodical to the Dauphin and published abundant praise of Louis XIV. The Mercure 's news reporting included distortions and propaganda intended to bolster and further entrench the king's foreign and domestic policies. The Mercure 's nouvelles, short stories presented as true recent events, constituted another type of 'fake news', one that often had a different effect, inviting the re-examination of social norms. The nouvelles appealed to the Mercure 's sizeable community of women readers by accentuating female agency and providing a vehicle for the exploration of scenarios of female empowerment.